Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation (GI) Terhadap Hasil Belajar Matematika Siswa SMP - Ika Kurniawati; Laila Hayati; Nurul Hikmah; Nyoman Sridana (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research is a quasi-experimental study that aims to determine the effect of the Group Investigation (GI) type of cooperative learning model on the mathematics learning outcomes of junior high school students. The population in this study were all VIII grade students of SMP Negeri 2 Kediri, which were divided into three classes. The research sample of two classes was taken by the purposive sampling technique. The data collection technique using tests and observation sheets. The experimental class uses a Group Investigation (GI) type of cooperative learning model and the control class uses a direct learning model. The sample in the study was class VIII-A as the experimental class and class VIIIB as the control class. The normality test and homogeneity test showed that the two samples were normally distributed and homogeneous. The data analysis using t test with show and so is rejected. So it can be concluded that there is an effect of the Group Investigation (GI) type of cooperative learning model on students mathematics learning outcomes. To find out how much the effect of the Group Investigation (GI) type of cooperative learning model has on the students mathematics learning outcomes, it can be done by using effect size calculations with Cohen’s formula and the calculation results are 1.18 including in the high category. This means that the application of the Group Investigation (GI) type of cooperative learning model has a high effect on the mathematics learning outcomes of VIII grade students of SMP Negeri 2 kediri academic year 2021/2022